Influence of CTAB surfactant on structural and optical properties of CuS and CdS nanoparticles by hydrothermal route. Issue 1 (1st January 2018) - Selvi, S. Sharon Tamil; Linet, J. Mary; Sagadevan, Suresh
ABSTRACT: Metal sulphide CuS and CdS nanoparticles capped with Cetyltrimethylammonium bromide (CTAB) were synthesized by hydrothermal method. Structural, morphological, chemical composition, optical and luminescent properties were evaluated by different analytical techniques. X-ray diffraction (XRD) analysis of the CTAB capped metal sulfide nanoparticles reveals the formation of hexagonal structure. High-resolution transmission electron microscopy (HRTEM) images show that the morphology of the capped copper sulphide samples consists of hexagonal structure and capped cadmium has spherical shape and also confirms the crystalline nature of the particles with distinct lattice fringes. In FTIR spectroscopy, the composition of the CTAB capped CuS and CdS nanoparticles have been confirmed. The analysis of photoluminescence (PL) and optical transition show a red shift due to the reduction of band gap energy and it is attributed to the low defects and high crystallinity. The optical studies indicate that CuS and CdS nanoparticles with CTAB can be suitable for optoelectronic devices and photovoltaic applications.